The Roles of Teacher and Parent Attitudes and Some Student Characteristics on Confidence in Learning Mathematics - Gün, Özge; Gün, Özge (Springer International Publishing, 2018)
This study mainly investigates the roles of students’ perceptions of their mother’s, father’s and teacher’s attitudes toward them as learners of mathematics, and gender and mathematics achievement on their confidence in learning mathematics. Moreover, in this study, students’ confidence is investigated according to gender and mathematics achievement. Data was collected from 1960 seventh grade students enrolled in 19 public elementary schools in a big city of Turkey. Results revealed that the difference between male and female students’ confidence in learning mathematics was not significant; but it was significant among achievement groups. On the other hand, the results of multiple regression analysis yielded that the model composed of five variables significantly predicted the confidence scores of students. In addition, it was found that mathematics achievement and students’ perceptions of their teachers’ attitudes toward them as learners of mathematics were the strongest predictors of their confidence in learning mathematics. © 2025 Elsevier B.V., All rights reserved.
Keywords: Confidence in Learning Mathematics; Gender; Mathematics Achievement; Teacher and Parent Attitude